Maria Mitchell - Butzer, Anna (North Mankato, Minnesota Capstone Press, a Capstone imprint, 2015)
Look up at the stars and explore the life of Maria Mitchell, the first female astronomer in the United States
A gift from book Africa
Famous People
1 2 13
Keywords: Mitchell, Maria -- 1818-1889; Mitchell, Maria -- 1818-1889 -- Juvenile literature; Women astronomers -- United States -- Biography -- Juvenile literature